Multimedia-Based Storytelling Learning Media Effectivity For Early Childhood’s Expressive Language Skill Development - Ghofur, Entep Hamdillah; Nurhayati, Sri (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The objective of this study is to evaluate the effectiveness of multimedia-based storytelling learning media in improving early childhood expressive language skills within the context of Early Childhood. This study used a quantitative approach, with pre-experimental research method using a one-group, pre- and post-test design. There were 50 children in the population, and there were 34 children in the sample. Data collection using observation, questionnaires and documentation. Using paired-sample t-tests to test hypotheses. The results indicated that Ha was approved, indicating that there was a 19.27% increase in the childrenâ€™s expressive language skill. Before and after treatment, there was an average difference in the expressive language capabilities of children. This demonstrates that multimedia-based learning media is effective at enhancing the expressive language skills of children. The study concludes that multimedia-based storytelling learning media is an effective tool for improving expressive language skills in early childhood.Â